Leading a Recovery-oriented Social Enterprise. (1st May 2015) - Raeburn, Toby; Hungerford, Catherine; Sayers, Jan; Escott, Phil; Lopez, Violeta; Cleary, Michelle
<x xml:space="preserve">Abstract</x> Recovery-oriented mental health services promote the principles of recovery, such as hope and optimism, and are characterized by a personalized approach to developing consumer self-determination. Nurse leaders are increasingly developing such services as social enterprises, but there is limited research on the leadership of these programs. Leading a recovery-oriented mental health nurse social enterprise requires visionary leadership, collaboration with consumers and local health providers, financial viability, and commitment to recovery-focused practice. This article describes the framework of an Australian mental health nursing social enterprise, including the service attributes and leadership lessons that have been learned from developing program sustainability.